Swarm Robotics - Coordination and Cooperation: Exploring Coordination and Cooperation Strategies in Swarm Robotics Systems for Achieving Collective Tasks (Journal of Computational Intelligence and Robotics, 2024)
Swarm robotics represents a fascinating area of research that draws inspiration from natural swarms, such as those observed in ant colonies or flocks of birds, to design robotic systems capable of achieving complex tasks through decentralized coordination and cooperation. This paper provides a comprehensive review of coordination and cooperation strategies in swarm robotics, focusing on how these approaches enable groups of robots to work together effectively. We discuss key concepts, such as swarm intelligence, collective behavior, and emergent phenomena, and highlight the advantages and challenges of using swarm robotics for various applications. Additionally, we review state-of-the-art research and recent advancements in the field, discussing the implications of these developments and identifying future research directions. Overall, this paper aims to provide insights into the current state of swarm robotics research and its potential for shaping the future of robotics and automation.